Urgensi Pembentukan Solusi Perlindungan Hukum bagi Penganut Agama dan Kepercayan Minoritas di Indonesia - Fery Rochmad Ramadhan; Fazal Akmal Musyarri; Maya Maulidya Nasmi (Jurnal Hukum Lex Generalis, 2020)
Indonesia is one of the countries that has a plurality of cultures in it, including religions embraced by the community. But the facts on the ground, only religion and belief of the majority are recognized by the community and the government. In the constitution, there is no law that requires every citizen to adhere to the six majority religions. That is, minority religions other than the six religions are allowed to develop in Indonesia as long as it is still within the limits of reasonableness. The Constitution which contains regulations that address religious freedom include Articles 28 and 29 of the Constitution of the Republic of Indonesia of 1945, Article 4 and Article 22 of Law No. 39 of 1999 on Human Rights and Law No. 1/PNPS/Year 1965 on Prevention of Abuse and/or Blasphemy. But if considered carefully, the Act contains statements that can cause misinterpretation. Such misinterpretation can be fatal especially for adherents of religious minorities outside the recognized religion in Indonesia. The most obvious consequence is discrimination against these minorities, both in terms of physical violence and in the field of administration. For example, the Ahmadiyya community is not calm in carrying out worship and the Sunda Wiwitan community which until now has been difficult to get official administrative papers because it is bumped with the problem of religious columns. During this time, religion and minority beliefs are less recognized and even tend to be considered heretical by society. In fact, they also have rights that include internal rights and external rights of religious freedom that should not be reduced by anyone. If traced back, it turns out that one of the causes is confusion in Law No. 1 / PNPS / Year 1965 on Prevention of Abuse and / or Blasphemy earlier.